Galaxy And Mass Assembly (GAMA): z ~ 0 galaxy luminosity function down to L ~ 106 L⊙ via clustering based redshift inference. Issue 4 (10th November 2021) - Karademir, Geray S; Taylor, Edward N; Blake, Chris; Baldry, Ivan K; Bellstedt, Sabine; Bilicki, Maciej; Brown, Michael J I; Cluver, Michelle E; Driver, Simon P; Hildebrandt, Hendrik; Holwerda, Benne W; Hopkins, Andrew M; et al.
ABSTRACT: In this study, we present a new experimental design using clustering-based redshift inference to measure the evolving galaxy luminosity function (GLF) spanning 5.5 decades from L ∼ 10 11.5 to 10 6  L⊙ . We use data from the Galaxy And Mass Assembly (GAMA) survey and the Kilo-Degree Survey (KiDS). We derive redshift distributions in bins of apparent magnitude to the limits of the GAMA-KiDS photometric catalogue: mr ≲ 23; more than a decade in luminosity beyond the limits of the GAMA spectroscopic redshift sample via clustering-based redshift inference. This technique uses spatial cross-correlation statistics for a reference set with known redshifts (in our case, the main GAMA sample) to derive the redshift distribution for the target ensemble. For the calibration of the redshift distribution, we use a simple parametrization with an adaptive normalization factor over the interval 0.005 < z < 0.48 to derive the clustering redshift results. We find that the GLF has a relatively constant power-law slope α ≈ −1.2 for −17 ≲ Mr ≲ −13, and then appears to steepen sharply for −13 ≲ Mr ≲ −10. This upturn appears to be where globular clusters (GCs) take over to dominate the source counts as a function of luminosity. Thus, we have mapped the GLF across the full range of the z ∼ 0 field galaxy population from the most luminous galaxies down to the GC scale.